Screening for acute HIV infections and estimating HIV incidence among female sex workers from low-grade venues in Guangxi, China. - Jianjun Li (Public Library of Science (PLoS), 2014)
Background Guangxi has become one of the provinces with the most severe HIV-1 epidemic in China, where heterosexual contact is the dominant transmission route. However, data of acute HIV infections and HIV incidence among female sex workers (FSWs) from low-grade venues are scant. Methods A cross-sectional survey was performed among FSWs from low-grade venues in Guangxi. HIV antibody screening was performed by rapid testing (RT). HIV antibody-negative specimens were screened by pooled nucleic acid amplification testing (NAAT) for acute HIV infections. HIV antibody-positive specimens were further analyzed by Western blot (WB), followed by an HIV-1 BED capture enzyme immunoassay (BED-CEIA) to identify the recent infections. HIV-1 incidence was estimated by the data of pooled NAAT and BED-CEIA, respectively. Results A total of 7936 FSWs were recruited and answered the questionnaires. We successfully collected the blood samples from 6469 (81.5%) participants, of which 139 (2.1%) were HIV antibody-positive and 6330 (97.9%) were HIV antibody-negative by RT. With pooled NAAT, 7 cases were found to be HIV RNA positive, representing an additional 5.0% of HIV-infected persons and an estimated HIV incidence of 1.45 (95% CI: 1.17-1.76) per 100 person years. There were 137 positive and 2 indeterminate by WB, of which 124 (90.5%) positive specimens were subjected to BED-CEIA testing identifying 28 recent infections. The HIV incidence determined by BED-CEIA testing was 1.04 (95% CI: 0.65-1.43) per 100 person years. The overall prevalence of HIV among FSWs from low-grade venues in Guangxi was 2.2% (95% CI: 1.9-2.6). Conclusions We found that the addition of HIV RNA screening to routine HIV antibody testing significantly improved the detection of HIV infection among FSWs from low-grade venues in Guangxi. Our findings also provided the useful baseline data of HIV incidence among this population for targeting local HIV prevention, intervention, monitoring and treatment.